The Impact of Covid-19 Pandemic on Islamic Health Insurance Market Returns: Empirical Evidence from Saudi Arabia - Fodol, Mohamed Zakaria; Aslan, Hakan (UI Scholars Hub, 2023)
This study aims to identify the impact of COVID-19 on the Cooperative Health Insurance (CHI) Market in Saudi Arabia by applying the Event Study Methodology. The announcement of the first positive case of COVID-19 in Saudi Arabia, which the Ministry of Health announced on March 2, 2020, is the health event identified in this study. The daily price of 24 cooperative health insurance companies listed on the Saudi Stock Market (Tadawul) with the market index (TASI) for the same period (June 05, 2018 - March 30, 2020) was collected. The abnormal returns are calculated by using Capital Asset Pricing Model (CAPM). The study found a negative effect of COVID-19 on the health insurance companies in Saudi Arabia during the first week of the anticipation period and continued until the event day. Negative abnormal returns persisted until the end of the total study period but were not statistically significant except for only three days in the post-event window (March 05, 08, and 09 2020). This means the Saudi cooperative insurance market was experiencing a period of anticipation and anxiety before the announcement of the first case of Covid-19; however, the information was insufficient and unconfirmed. During the adjustment window, the market tried to adjust itself and react to the event efficiently, but it could not do so. According to the efficient market hypothesis, the Saudi cooperative insurance market is not fully efficient. This study only sheds light on the Corona pandemic's effects in a short period. Indeed, the need for extensive future research remains. The results of this study are useful to Islamic insurance investors, Takaful operators, regulators in the Islamic insurance markets (Takaful and Cooperative), and researchers and academicians alike.